PENDIDIKAN AGAMA BAGI ANAK DALAM KELUARGA DI GAMPONG ANEUK GALONG BARO, ACEH BESAR - Aulia Rahmi (IAIN Padangsidimpuan, 2018)
Religious Education in family environment is the education that’s given by parent to their children in their family environment for building children’s personality become a good muslim by changing their attitude and their behaviour that appropriate with Islamic Education. The aims of the study was to know parent’s manner in training their children about religious in Gampong Aneuk Galong Baro. This research was conducted by using descriptive qualitative methode and the isntrument of the data was interview, observation and documentation. The finding of this study was revealed that religious education for children in family environment of gampong Aneuk Galong Baro was be begun with the aqidah education (aqidah is not attitude but the faith ), because aqidah (the faith) was the core of someone’s basic faith that must be instilled to the children early. Furthermore,it was the worship education ( ibadah). In the worship education parents focus on teaching their children about praying, reading Holy Qur’an and also fasting. The last, parents teach their children about attitude ( Akhlak) because the result of the faith and good worship, it can be seen in their daily attitude